Pengembangan Dimensi Empati sebagai Upaya Peningkatan Kualitas Pelayanan Publik di Kantor Kecamatan Gubeng Surabaya - Khanifatul Khusna (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2017)
This study aimed to describe the dimensions of empathy on public service at the Gubeng District Office, Surabaya. Based on the investigation of the Ombudsman Indonesia to the public service indicates that there was still mal-administration in Gubeng district Office at Surabaya City. In addition, the number of public complaints in the Gubeng District Office is higher compared than the other District of district Offices in Surabaya. This research is using descriptive qualitative as a method, and the technique of collecting data is using interviews and observations. The leader of Gubeng District office is a key person and than used snowball saplingin this research. While the validity of the data is using techniques transform credibility and dependency. The Dimension of empathy measurement is using four indicators: the ability to understand the society, service orientation, developing others and utilizing diversity. The results of data analysis showed that the dimensions of empathy at the Gubeng District Office still negative. Indicators of the ability to understand the society, serves orientation and utilize the diversity is still negative. Whereas developing the others indicator still positive. After knowing the dimensions of empathy in Gubeng District Office still negative then exploration about stimulus and obstacle factors. The stimulus factors to develop the empathy are working relationship, leadership, time services, and responsibility. While the obstacle factors are learning, physical working environment, and family conflicts. Based on these factors, the development of dimension empathy which conducted by the leader of Gubeng District and his employee is monitoring and internal evaluation.The sub-leaders often take evaluation participatory in order to ask all employee be able to do their job.